The ICT basic skills: Contribution to student social media utilization activities - Supardi Supardi; Juhji Juhji; Intan Azkiyah; Birru Muqdamien; Aan Ansori; Iwan Kurniawan; Ahmad Fitriadi Sari (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study aimed to analyze the contribution of Information and Communications Technology (ICT) basic skills to student social media utilization activities. Quantitative research was determined as a method with regression analysis. A total of 144 students selected randomly participated in this research. The research instrument used a five-scale questionnaire, consisting of 32 items of ICT skill instruments and 20 items for social media utilization instruments. The results showed a high level of ICT students' basic skills and social media use activities. There is a contribution of basic ICT skills to student social media utilization activities. The higher of the basic skill of ICT causes the higher the level of activity utilization of their social media. Research recommendations suggest efforts to improve students' basic ICT skills.